Eco-Industrial Parks of the Lviv Region as a Factor of the Inclusive Development of the Western Region of Ukraine - Lіubov G. Kvasnii; Olena V. Moravska; Oksana Soltysik; Yurii O. Shulzhyk; Oresta Ya. Shcherban; Stah O. Vovk (Studia Regionalne i Lokalne)
The article examines the key points of creating eco-industrial parks in the Lviv region and reforming existing industrial parks according to the principles of circular and green economy. The intensive increase in the number of industrial enterprises in the Lviv region is due to the active relocation of enterprises from the war zone of Ukraine. The purpose of the article is to justify the feasibility of creating eco-industrial parks in the Lviv region according to the principles of circular and green economy. The authors recommend the principles of selecting industrial enterprises in the territories of industrial parks, taking into account industrial symbiosis. As part of research cooperation, we conducted and researched the stages of the design, construction, and development of industrial parks in the Lviv region of Ukraine. Practical recommendations have been developed and proposed for the creation and implementation of the production of environmentally-friendly products with further processing and the secondary cycle of waste use in order to reduce the use of natural resources and environmental pollution, and increase the socioeconomic development of the western region of Ukraine.